2020
DOI: 10.1097/mao.0000000000002704
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Findings in Children Suspected to Have Been Exposed to the Zika Virus in the Intrauterine Period

Abstract: Objective: To evaluate auditory manifestations in children born to mothers who had exanthema during pregnancy, suspected to have been exposed to the Zika virus (ZIKV). Study Design: Prospective observational. Setting: Tertiary referral center. Patients: Children born in Rio de Janeiro, Brazil, between April 2016 and September 2017, who were referred for newborn h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Another Brazilian study conducted in the city of Rio de Janeiro from April 2016 to September 2017 revealed a rate of 5.1% of audiological alterations among the 78 children whose responses to automated brainstem auditory-evoked potential testing were evaluated in the first six months and at 12 months of age. This study similarly observed no progressive loss of hearing [9]. Overall, our findings align with the latest recommendations from the US Centers for Disease Control and Prevention (CDC) guidance for diagnosis, evaluation and management of infants with CZS, which no longer recommends a diagnostic ABR in the first year, if auditory screening is passed by automated ABR [30].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another Brazilian study conducted in the city of Rio de Janeiro from April 2016 to September 2017 revealed a rate of 5.1% of audiological alterations among the 78 children whose responses to automated brainstem auditory-evoked potential testing were evaluated in the first six months and at 12 months of age. This study similarly observed no progressive loss of hearing [9]. Overall, our findings align with the latest recommendations from the US Centers for Disease Control and Prevention (CDC) guidance for diagnosis, evaluation and management of infants with CZS, which no longer recommends a diagnostic ABR in the first year, if auditory screening is passed by automated ABR [30].…”
Section: Discussionsupporting
confidence: 85%
“…Current understanding of the syndrome is further limited by the lack of published longitudinal studies of children with intrauterine exposure to Zika virus [5] , [6] . In addition to classical cortical neurological damage, congenital Zika virus infection may also lead to functional disabilities, such as swallowing disorders, visual impairment in the absence of structural ocular abnormalities [7] , and hearing loss [4] , [8] , [9] , [10] , [11] . While there is strong evidence that children congenitally infected with Zika virus exhibit abnormalities at the time of delivery, several studies have reported late-onset microcephaly among infants born with a normal head circumference, raising the hypothesis that there may be continued viral activity in neural tissue, even after birth [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The absence of detectable viral RNA and loss of antibodies has been described in a human infant with ocular defects and CZS (19). This further highlights the difficulty of determining the long-term impact of CZS, as a child who presents to the clinic with neurological or ocular abnormalities, but without a known history of ZIKV infection during pregnancy or detectable ZIKV or antibody, may pose difficulty establishing a causal relationship between the defect and in utero ZIKV exposure (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies evaluated hearing in the ZIKV-exposed infants beyond neonatal screenings, sensorineural hearing loss (SNHL) appears to be infrequent and occurs in infants with microcephaly and other severe anomalies of CZS ( Leal et al, 2016 ). Among 70 children with laboratory-confirmed ZIKV infection and microcephaly in Brazil, 5.8% presented hearing loss (SNHL) ( Faria et al, 2020 ). This percentage was 3.8% among 78 prospectively ascertained infants likely exposed to the ZIKV in utero ( Faria et al, 2020 ).…”
Section: Congenital Zika Syndromementioning
confidence: 99%
“…Among 70 children with laboratory-confirmed ZIKV infection and microcephaly in Brazil, 5.8% presented hearing loss (SNHL) ( Faria et al, 2020 ). This percentage was 3.8% among 78 prospectively ascertained infants likely exposed to the ZIKV in utero ( Faria et al, 2020 ). Although we predicted that the conductive hearing loss secondary to otitis, upper airway congestion, and infections would be increased in these infants, no data are yet available.…”
Section: Congenital Zika Syndromementioning
confidence: 99%